2021
DOI: 10.3389/fneur.2021.670784
|View full text |Cite
|
Sign up to set email alerts
|

The Clinicopathological Distinction Between Seropositive and Seronegative Immune-Mediated Necrotizing Myopathy in China

Abstract: Objectives: The present study aimed to compare the clinicopathological features of patients with seronegative immune-mediated necrotizing myopathy (IMNM) and those positive for anti-signal recognition particle (SRP) or anti-3-hydroxy-3-methylglutarylcoenzyme-a reductase (HMGCR) antibodies.Methods: We retrospectively analyzed the data of patients with IMNM treated in the Neurology Department of Tongji Hospital from January 1, 2013, to December 31, 2019.Results: Among the 117 patients with IMNM, 30.8% (36/117) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
1
13
0
2
Order By: Relevance
“…Skeletal muscle biopsies obtained from patients with IMNM show prominent myofiber necrosis and regeneration as well as a scarcity of inflammatory infiltrates 35,36 . Necrotic myofibers exhibit the characteristics of different stages of necrotic and regenerating myofibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle biopsies obtained from patients with IMNM show prominent myofiber necrosis and regeneration as well as a scarcity of inflammatory infiltrates 35,36 . Necrotic myofibers exhibit the characteristics of different stages of necrotic and regenerating myofibers.…”
Section: Discussionmentioning
confidence: 99%
“…show prominent myofiber necrosis and regeneration as well as a scarcity of inflammatory infiltrates. 35,36 Necrotic myofibers exhibit the characteristics of different stages of necrotic and regenerating myofibers. In this study, we observed that both atrophic upregulated in IMNM compared with healthy controls.…”
Section: Skeletal Muscle Biopsies Obtained From Patients With Imnmmentioning
confidence: 99%
“…При отсутствии анти-SRP частота интерстициального поражения легких достигала 10-20%, а при их наличии составляла только 5% [8]. Кроме того, наличие этих антител может сопровождаться нарушениями ритма и проводимости [23]. Анти-SRP-позитивный вариант аутоиммунной некротизирующей миопатии характеризуется более частыми экстрамышечными поражениями и дисфагией [4,8].…”
Section: клиническая картинаunclassified
“…В настоящее время данных об особенностях клинической картины СИНАМ в зависимости от серологического варианта недостаточно, так как они были получены при анализе единичных публикаций [14,23]. Тем не менее, результаты серологического исследования позволяют окончательно подтвердить диагноз СИНАМ.…”
Section: клиническая картинаunclassified
“…Currently, two principle categories of IMNM, anti-signal recognition particle (SRP) autoantibodies-IMNM (SRP-IMNM) and anti-3-hydroxy-3-methylglutaryl-coa reductase (HMGCR) autoantibodies-IMNM (HMGCR-IMNM) (5,6), account for the largest proportion of IMNM and are relatively the most described. Other subtypes, including seronegative IMNM, connective tissue disease-related IMNM, statin-related IMNM, cancer-related IMNM, and immune checkpoint inhibitorsinduced IMNM are also reported (7)(8)(9)(10)(11)(12). The detection of serum anti-SRP autoantibodies in IIM is much earlier than that of anti-HMGCR autoantibodies.…”
Section: Introductionmentioning
confidence: 99%